Menakar Peran Bantuan Sosial untuk Mewujudkan Ketahanan Pangan di Jawa Tengah pada Rumah Tangga Miskin Multidimensi - Muthia, Azka (Seminar Nasional Official Statistics, 2025)
Poverty is a multidimensional phenomenon strongly linked to food insecurity. In Central Java Province, there has been a noticeable increase in food consumption inadequacy, coupled with the issue of misdirected aid recipients. The provincial government's policy focus is poverty alleviation and enhancing food security, primarily through social assistance programs. This research utilizes March 2022 Susenas data and employs Propensity Score Matching (PSM) and ordinal logistic regression methods. The analysis reveals that a multidimensional approach to poverty significantly impacts food security in Central Java. Moreover, using Propensity Score Matching (PSM), the results show that the social assistance provided has no positive effect on the food access and food utilization dimensions for multidimensional poor households, except for those receiving both food and non-food assistance. This highlights an ongoing issue of misdirected aid. Additionally, while social assistance increases the quantity of food, it does not lead to improvements in food quality. One key implication of this study is the critical need to ensure that social assistance is accurately targeted to households. To address this, the government should consider developing a program that empowers the integrated data system of Central Java, incorporating a more precise spatial mapping approach.